PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 21 BALAI MAKAM KECAMATAN MANDAU - Syarifah, Syarifah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the low student learning outcomes in learning natural sciences at SD Negeri 21 Balai MakamKecamatan Mandau. The purpose of this study is to improve the learning process and improve student learning outcomes byapplying cooperative learning models Type Two Stay Two Stray (TSTS). The study was conducted in two cycles. The subjects ofthis study were 33 grade V students. This research was conducted in the odd semester of the 2016/2017 school year in August2017. Student learning outcomes in cycle 1 obtained an average of 74.53 and in cycle 2 it was obtained an average of 82.25 withan average increase in student learning outcomes of 25.83%. So it can be concluded that with the application of the Cooperativelearning model Type TSTS can improve the learning outcomes of Natural Sciences grade V students of SD Negeri 21 BalaiMakam Kecamatan Mandau.